The Inhibition of CD40/CD154 Costimulatory Signaling in the Prevention of Renal Transplant Rejection in Nonhuman Primates: A Systematic Review and Meta Analysis - Perrin, Steven; Magill, Marianne (Frontiers in Immunology, 2022)
The prevention of allograft transplant rejection by inhibition of the CD40/CD40L costimulatory pathway has been described in several species. We searched pubmed for studies reporting the prevention of kidney transplant rejection in nonhuman primates utilizing either anti CD40 or anti CD40L (CD154) treatment. Inclusion of data required treatment with anti CD40 or anti CD154 as monotherapy treatment arms, full text available, studies conducted in nonhuman primate species, the transplant was renal transplantation, sufficient duration of treatment to assess long term rejection, and the reporting of individual graft survival or survival duration. Eleven publications were included in the study. Rejection free survival was calculated using the Kaplan-Meier (KM) life test methods to estimate the survival functions. The 95% CI for the medians was also calculated. A log-rank test was used to test the equality of the survival curves between control and treatment arms (CD40 and CD154). The hazard ratio for CD154 compared to CD40 and 95% CI was calculated using a Cox proportional-hazards model including treatment as the covariate to assess the magnitude of the treatment effect. Both anti CD40 and anti CD154 treatments prevented acute and long term graft rejection. The median (95% CI) rejection free survival was 131 days (84,169 days) in the anti CD40 treated animals and 352 days (173,710 days) in the anti CD154 treated animals. Median survival in the untreated animals was 6 days. The inhibition of transplant rejection was more durable in the anti CD154 group compared to the anti CD40 group after cessation of treatment The median (95% CI) rejection free survival after cessation of treatment was 60 days (21,80 days) in the anti CD40 treated animals and 230 days (84,552 days) in the anti CD154 treated animals.